Which Boundary Objects are Applicable to Service Innovation? A Dynamic Capability Perspective - Malsbender, Andrea; Plattfaut, Ralf; Niehaves, Bjoern; Becker, Joerg (Proceedings of the 47th Hawaii International Conference on System Sciences (HICSS-47), 2014)
Service Innovation has become a focal point of attention for managers. Hence, organizations need to implement a convenient innovation strategy to remain competitive in constantly changing market environments. To identify, design and implement possible service innovation, organizations already successfully cooperate with external partners, suppliers, customers or internally through different functional departments. In so doing, organizational boundaries occur with respect to unequally distributed knowledge. This disparity needs to be overcome by spanning different groups through technology. In this article, we analyze what kind of IT artifact, so called boundary object, can be used within a service innovation. To this end, we conduct an empirical investigation in 500 German SMEs with the aim of identifying suitable boundary objects for each stage of a service innovation process. Drawing from the dynamic capability and boundary spanning theory we identify four boundary object types and reveal an insufficient utilization of them.